2021
DOI: 10.1021/acsami.1c12675
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Radiation-Assisted Drug Delivery Nanoplatform to Realize Blood–Brain Barrier Crossing and Protection for Parkinsonian Therapy

Abstract: Mitochondrial dysfunction, which is directly involved in Parkinson’s disease (PD), is characterized by the production of reactive oxygen species (ROS) and aberrant energy metabolism. Thus, regulating mitochondrial function might be an effective strategy to treat PD. However, the blood–brain barrier (BBB) presents a significant challenge for the intracerebral delivery of drugs. Here, we synthesized a zeolitic imidazolate framework 8-coated Prussian blue nanocomposite (ZIF-8@PB), which was encapsulated with quer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…The physiological state of the brain is quite different to that of other organs because the BBB is a primary obstacle for drug delivery to the brain [25,26]. For this reason, various delivery platforms have been investigated to improve the penetration and/or transport of bioactive agents [26][27][28][29][30][31][32][33][34][35][36][41][42][43][44][45][46][47]. For example, surfactants such as polysorbate 80 have been used to allow nanoparticles or drug carriers to penetrate the BBB [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The physiological state of the brain is quite different to that of other organs because the BBB is a primary obstacle for drug delivery to the brain [25,26]. For this reason, various delivery platforms have been investigated to improve the penetration and/or transport of bioactive agents [26][27][28][29][30][31][32][33][34][35][36][41][42][43][44][45][46][47]. For example, surfactants such as polysorbate 80 have been used to allow nanoparticles or drug carriers to penetrate the BBB [41][42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies such as OX-26 can be used to decorate nanoparticles for the brain delivery of bioactive agents [44]. Liu et al reported that zeolite imidazolate framework 8-based nanocomposites delivered quercetin to the brain, reduced oxidative stress and reversed dopaminergic neuronal damage [34]. They argued that nanocomposites can be used for neurodegenerative diseases without any damage to the normal tissues according to the results found in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanotechnology has developed rapidly in recent years, and natural products, including herbal therapy based on nanotechnology, are becoming increasingly popular and are showing very broad application prospects ( Liu et al, 2021 ; Zhang et al, 2021 ; Zhu et al, 2021 ). Nanotechnology usually refers to the use of nanomaterials with sizes between 1 and 100 nm, which can be classified as organic and inorganic nanoparticles.…”
Section: Natural Products Based On Nanotechnologymentioning
confidence: 99%